How infant spaces are accommodated and incorporated in the home of selected Filipino middle class families - Pile, Aizel Gem; Faustino, Johanna Acab. (Quezon City UP College of Home Economics, 2012)
Different infant spaces emerge in the home at the arrival of an infant. The purpose of this study is to determine the idea or concept of a Filipino nursery among selected middle class families. The study aimed to identify the needs of an infant and see how the respondents accomodate and incorporate infant spaces in their home. This was done through determining the strategies used by the selected families and discovering the reasons behind the adapted strategy. As such, the study used the descriptive case study design for this research with the use of purposive sampling. The respondents for the survey questionnaire were 10 middle-class families based from Laguna. There were 2 respondents who have a child 0 to 1 year and 6 months old for the interview and photo documentation. The results of the study showed that child rearing activities are done in multiple areas in the home. The parents' bedroom is the most used area followed by the living room. There is multi-functionality between the areas and rooms creating semi-fixed feature spaces. Yet, even with constant change in the space, the parents take into consideration the accessibility and comfort of the infant spaces. This is further guaranteed by their choice of durable and quality furniture for their infants. The parents have preconceptions on the idea of the nursery as a separate bedroom for the infant, which by definition is correct. However, the nursery that most selected Filipino middle-class families had formed and some prefer is a form of shared nursery wherein the parents can provide constant guidance to the infant. The infant, who is well loved in Filipino culture, is viewed as the caretaker of the future. As such the Filipino parents value their responsibility to provide and nourish the infants with care. It is recommended that similar studies with different demoraphic location or socio-economic status be made for comparison of data and results.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Children's rooms -- Philippines; Space (Architecture).